Isolation and Identification of Lactic Acid Bacteria from Channa sp. as Potential Probiotic - Bayu, Hendi Hendra; Irwanto, Riko; Dalimunthe, Nurzaidah Putri; Lingga, Rahmad (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Lactic acid bacteria (LAB) are a group of bacteria that are naturally present in the digestive tract of vertebrates, including fish such as Channa sp. Lactic acid bacteria are considered the most suitable microbes for use as probiotics. Probiotics can produce antimicrobial metabolites so that can improve the microbial balance in the digestive tract. It is believed that Channa sp. harbors LAB in its digestive tract, which may have probiotic potential and produce antimicrobial metabolites that can inhibit pathogenic bacteria. The aim of this study was to isolate and identify LAB from the intestines of Channa sp. The research involved several steps, including sample preparation, LAB isolation, characterization, and purification of bacterial isolates, biochemical tests, temperature resistance tests, antimicrobial tests, haemolysis tests, lactic acid production tests, and cholesterol-lowering activity tests. Eight LAB isolates with potential probiotic characteristics were isolated and identified as the genus Lactobacillus, which are gram-positive bacteria that produce lactic acid during culture